Scalable manufacturing of immiscible AlBi alloy by self-assembled nanoparticles. (15th May 2018) - Cao, Chezheng; Liu, Weiqing; Liu, Zhiwei; Xu, Jiaquan; Hwang, Injoo; De Rosa, Igor; Li, Xiaochun
Abstract: Immiscible AlBi alloy, with a miscibility gap in the liquid state is not only scientifically important, but also it can offer outstanding self-lubricating properties. However, it is still difficult to control the distribution and size of minority Bi phase during cooling and solidification. Here we show that by applying a scalable molten salt assisted incorporation process, TiC nanoparticles can be incorporated in Al matrix to produce Al-TiC master nanocomposites, which can be readily used to process AlBi immiscible alloy and restrict the size of minority Bi phase. TiC nanoparticles can be self-assembled on the AlBi interface and restrict Bi phase size substantially. In addition, submicron minority Bi phase can be achieved by combining the addition of nanoparticles with high cooling rates. Mechanical properties of AlBi immiscible alloys can be further enhanced by the addition of Cu element and cold rolling. Graphical abstract: Unlabelled Image Highlights: Master Al-TiC nanocomposites are fabricated by a novel salt assisted self-incorporation method. Master Al-TiC nanocomposites are utilized to process AlBi immiscible alloys. TiC nanoparticles can self-assemble on the AlBi interface and refine microstructures. With nanoparticles and higher cooling rates, the size of Bi phase can be reduced to sub-micron. Mechanical properties can be enhanced by alloying and cold rolling.